"A Mining Town Needs Brothels": Gossip and the Rhetoric of Sex Work in a Wild West Mining Community. Issue 5 (19th October 2016) - Branstetter, Heather Lee
Abstract : This essay explores the role of rhetoric in an American West town that embraced prostitution as integral to its sense of identity from 1884–1991, when its economy began to shift from silver mining to tourism. The circulation of social values negotiated through gossip enabled a century-long period during which brothels flourished in an illegal yet decriminalized way. Even though the madams and sex workers were subject to spatial restrictions and the whims of local political and regulatory power, they managed to harness the available means of opportunistic discourse often overlooked in rhetorical analysis. I highlight the influence of the semi-private exchange of rumor and normative small talk. Arising out of spatial and qualitative public memory, gossip can be a persuasive force that harmonizes community needs across past, present, and future.